Under Utilization of Foreign Aid In India: An Issue of Concern - Phull, Kulwant Singh (Indian Journal of Finance, 2009)
The article "Under-Utilisation of Foreign Aid in India: An Issue of Concern" is an endeavour to highlight the fact that foreign aid in India, obtained with lot of difficulties, has shown a fluctuating trend in its utilisation and remained most of the times under-utilised. Consequently, a huge sum of authorised aid amounting Rs. 75586.55 crore up to the end-March 2006 remained unutilised, due to the various undue, unnecessary and inordinate delays like: under-provisioning, lack of commitment and coordination on the part of implementing agencies, inadequate counterpart rupee funding, protracted procurement and contracting delays, start up, and other procedural delays etc., in the implementation of externally aided projects in the country. It could have relived 13.54 percent of India’s total external debt amounting Rs. 5, 58,372 crore during the same period or have helped to achieve the Millennium Development Goals in the country to some extent, if it has been fully utilised, besides saving the commitment charges paid for the un-utilised loans.